[RETRACTED ARTICLE] Surrogate’s Decision Making Regarding Treatments of Critically Ill Muslim Older Patients at the End of Life - Jehloh, Latifah -; Nilmanat, Kittikorn; Kongsuwan, Waraporn (Princess of Naradhiwas University Journal, 2019)
This article has been Retracted at the request of the Editor-in-Chief. This research aimed to study treatment-related decision of surrogates of critically ill Muslim older patients at the end of life period. A sample of 120 surrogates of critically ill older persons receiving care in critical care and medical units at a provincial hospital were purposively selected. The questionnaire was use to collected data on personal characteristics and treatment-related decision making. Descriptive analysis and content were performed. Alpha’s Cronbach of instrument’s validity was 0.87. The results revealed that 84.17% of the surrogates made a decision to continue life-prolonging treatments, either by giving full or limited treatments, 15.83% decided to withdraw the treatments, and 76.67% decided to give comfort treatments while withdrawing or continuing life-prolonging treatments. The reasons to prolong life with full treatment included surrogate’s wish to give the patient the best possible treatment, hoping for revival, being unable to accept death, and past experience. The reasons to prolong life with limited treatments included patient sufferings related to treatments, patient’s wish and patient’s advancing age. The decisions to discontinue treatments and take the patients home were based on a patient’s wish to die at home, deterioration of symptoms, andpatient sufferings. Surrogates who decided to give comfort treatments made this decision based on patient suffering related to critical illness and treatments. They limited physically distressing medical procedure and allowed pain killers to relieve patient suffering during the end of life.